Experimental Studies Involving the Impact of Solar Radiation on the Properties of Expanded Graphite Polystyrene - Paweł Krause; Artur Nowoświat (Energies, 2019)
This article presents the research studies aimed at identifying the behavior of expanded polystyrene with the addition of graphite in the conditions of exposure to solar radiation. For this purpose, a series of in situ tests and laboratory studies were carried out. Three types of material were tested, i.e. expanded polystyrene (EPS) (white polystyrene), polystyrene with the addition of graphite (gray polystyrene) and two-layer polystyrene (gray bottom layer and white top layer). Temperature distributions on the surfaces of the panels in field and laboratory conditions were determined. The distributions of temperature were recorded at varied wind impact (field conditions and laboratory conditions) and at varied impact of solar radiation (laboratory conditions). Based on the conducted experiments, differences in temperature distribution on the surfaces of the tested panels were determined. In addition, geometric changes and deformation levels of the tested white and gray expanded polystyrene panels exposed to artificial sun radiation were determined in laboratory conditions.